The Classical Commentary in Renaissance France: Bilingual, Mixed-Language, and Translated Editions - White, Paul (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2018)
This article analyzes the dynamic interactions of Latin and the vernacular in commentary editions of the Latin classics printed in France before 1600, addressing questions of readership, intended uses, and actual uses. Beginning with the output of Antoine Vérard, it explores the different possibilities for translating Latin commentaries in the early decades of French printing, and the reconfigurations of layout and commentary discourse between languages. There follows a discussion of bilingual and mixed-language editions intended for use in the Latin grammar class and beyond (Mathurin Cordier, Charles Estienne, Jean Herisson, Guillaume Durand, and Pierre Davantès). Particular attention is given to evidence for the uses of such texts in the form of contemporary readers’ annotations and marks of use.